Hepatic and renal evaluation in rats submitted to chronic administration of botulinum toxin tip A in the submandibular salivary gland (Research, Society and Development, 2022)
Botulinum toxin type A (BTX-A) has been used as one of the treatment options to control sialorrhea, however its systemic effects after chronic treatment are not yet known. Therefore, the objective was to evaluate histopathological alterations of the hepatic and renal parenchyma of rats chronically treated with botulinum toxin type A injection in the submandibular-sublingual complex. Twenty-one adult Wistar rats were divided into three groups with 7 animals each: control; groups BTX-12 and BTX-35, which received 3 intercalated applications of BTX-A. The BTX-12 and BTX-35 groups were analyzed at 12 and 35 days after treatment, respectively. Histopathological and histomorphometric analyzes of the liver and kidney of all animals in the groups were performed. In the liver, histopathological changes were observed characterized by hypertrophy of hepatocytes, pyknosis, centrilobular degeneration and lymphohistiocytic, neutrophilic infiltrate and in the kidneys, decreased capsular space, glomerulopathies and degenerations in nephrons and convoluted tubules were observed. Histomorphometry revealed a reduction in the size of the hepatocyte nuclei and also of the renal glomerulus. Therefore, it can be suggested that botulinum toxin type A administered to rats for the treatment of sialorrhea has hepatotoxic and nephrotoxic potential.